Promiscuity and selectivity in covalent enzyme inhibition: a systematic study of electrophilic fragments - Jöst, Christian; Nitsche, Christoph; Scholz, Therese; Roux, Lionel; Klein, Christian D. (Journal of medicinal chemistry, 2014)
Covalent ligand-target interactions offer significant pharmacological advantages. However, off-target reactivity of the reactive groups, which usually have electrophilic properties, must be minimized, and the selectivity of irreversible inhibitors is a crucial requirement. We therefore performed a systematic study to determine the selectivity of several electrophilic groups that can be used as building blocks for covalently binding ligands. Six reactive groups with modulated electrophilicity were combined with 11 nonreactive moieties, resulting in a small combinatorial library of 72 fragment-like compounds. These compounds were screened against a group of 11 enzyme targets to assess their selectivity and their potential for promiscuous binding to proteins. The assay results showed a considerably lower degree of promiscuity than initially expected, even for those members of the screening collection that contain supposedly highly reactive electrophiles.